2006
DOI: 10.1002/smll.200600130
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence‐Emission Control of Single CdSe Nanocrystals Using Gold‐Modified AFM Tips

Abstract: A new means of switching the fluorescence emission of a single nanocrystal by intervention of a gold‐modified AFM tip, and the luminescence properties (see TIRFM image) as a function of distance between the single quantum dot and the tip, are presented. Significant luminescence enhancement due to exciton–plasmon coupling was detected. This is important in controlling molecular individuals with applications ranging from microarrays to manipulation of single reporter molecules. TIRFM: Total‐internal‐reflection f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 43 publications
0
33
1
1
Order By: Relevance
“…It has been shown that quenching can be utilized to probe distances in the nanometer or sub-nanometer range (Berndt et al, 2010;Marme et al, 2003;Selvin, 2000). The impact of metal tips or nanostructures close to fluorophores has been well characterized (Ambrose et al, 1994;Anger et al, 2006;Ebenstein et al, 2006;Eckel et al, 2007;Krug et al, 2005;Kuehn et al, 2006;Xie & Dunn, 1994;Yoskovitz et al, 2011). Here, we exploit the quenching of organic fluorophores by sharp ndoped silicon tips to record topographical and optical images simultaneously with nanometer resolution.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that quenching can be utilized to probe distances in the nanometer or sub-nanometer range (Berndt et al, 2010;Marme et al, 2003;Selvin, 2000). The impact of metal tips or nanostructures close to fluorophores has been well characterized (Ambrose et al, 1994;Anger et al, 2006;Ebenstein et al, 2006;Eckel et al, 2007;Krug et al, 2005;Kuehn et al, 2006;Xie & Dunn, 1994;Yoskovitz et al, 2011). Here, we exploit the quenching of organic fluorophores by sharp ndoped silicon tips to record topographical and optical images simultaneously with nanometer resolution.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32] Experiments on model systems formed by single dipole emitters such as molecules and semiconductor nanocrystals and spherical metal particles revealed a distance dependent interplay between competing enhancement and quenching processes. [33][34][35][36][37][38][39] Here the role of emitter dipole orientation for the interplay between quenching and fluorescence enhancement becomes apparent. 40 Small cone angles in tip-shaped metal structure are predicted to reduce energy dissipation as compared to spherical particles.…”
Section: Tip-enhanced Fluorescence-mentioning
confidence: 99%
“…It has been shown that the combination of AFM and fluorescence microscopy offers new opportunities to gather multidimensional data from a given system [31][32][33][34][35][36] , but it can also make use of fluorescence modulation effects which arise from the presence of the sharp AFM probe in the vicinity of fluorescent molecules. These effects include the enhancement [11][12][13]16 and quenching 17,18,20,22,23,37,38 of the fluorescence and a change in the fluorescence lifetime 23 . Since both enhancement and quenching are highly localized phenomena, they can lead to much higher resolution than the diffraction limit dictates for optical imaging.…”
Section: Introductionmentioning
confidence: 98%
“…The basis for all high resolution near field applications is the emission behavior of fluorophores on surfaces in close proximity to a sharp tip. This behavior has been studied experimentally as well as theoretically [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] . The fluorescence properties of fluorophores (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation